A taqman duplex quantitative PCR method for detecting Klebsiella pneumoniae has been developed based on pan-genome analysis - Li, Zenghui; Hua, Mingming; Liu, Xinyu; Wang, Yi; Kong, Mengmeng; Hu, Zheng; Yang, Bo (Penerbit Universiti Kebangsaan Malaysia, 2025)
Klebsiella pneumoniae is a significant pathogen capable of causing infections in the respiratory, urinary, and bloodstream. In this study, bioinformatics-based pan-genome analysis identified specific and conserved LptD and MerR protein gene sequences in K. pneumoniae. Based on these sequences, specific primers and probes were designed, and the reaction system and conditions were optimized to establish a TaqMan probe-based duplex real-time quantitative PCR method for detecting K. pneumoniae. The method was tested on genomic DNA from 14 common pathogens and negative controls. The results showed that only the genomic DNA of K. pneumoniae was positive, while all other samples were negative. The detection limits for LptD and MerR gene-positive standard plasmid DNA were 5.28 × 101 copies/μL and 5.78 × 101 copies/μL, respectively, and the coefficient of variation for Ct values between intra- and inter-gene groups was less than 3%. These results indicate that the established TaqMan probe-based duplex real-time quantitative PCR method can specifically and rapidly detect K. pneumoniae, which is of significant importance for clinical diagnosis and treatment.